Locus revealed: Painlessness via loss of NaV1.7 at central terminals of sensory neurons - Simonetti, Manuela; Kuner, Rohini (Neuron, 2021)
How genetic loss of the sodium channel NaV1.7 results in painlessness is puzzling. MacDonald et al. (2021) demonstrate that instead of impairing peripheral excitability, NaV1.7 channels at central terminals of pain-sensing afferents play a pivotal role in the balance between pain and analgesia.